Adsorptive Removal of Hexavalent Chromium by Diphenylcarbazide-Grafted Macadamia Nutshell Powder - Londolani C. Maremeni; Sekomeng J. Modise; Fanyana M. Mtunzi; Michael J. Klink; Vusumzi E. Pakade (Bioinorganic Chemistry and Applications)
Macadamia nutshell powder oxidized by hydrogen peroxide solutions (MHP) was functionalized by immobilizing 1,5′-diphenylcarbazide (DPC) on its surface. The effectiveness of grafting was confirmed by the Fourier transform infrared spectrum due to the presence of NH and C=C stretches at 3361, 1591, and 1486 cm−1, respectively, on the grafted material which were absent in the nongrafted material. Thermogravimetric analysis revealed that the presence of DPC on the surface of Macadamia shells lowered the thermal stability from 300°C to about 180°C owing to the volatile nature of DPC. Surface roughness as a result of grafting was appreciated on the scanning electron microscopy images. Parameters influencing the adsorptive removal of Cr(VI) were examined and found to be optimal at pH 2, 120 min, 150 mg/L, and 2.5 g/L. Grafting MHP with DPC leads to an increase in the Langmuir monolayer capacity from 37.74 to 72.12 mg/g. Grafting MHP with DPC produced adsorbent with improved removal efficiency for Cr(VI).